Bacillus thuringiensis Suppresses the Humoral Immune System to Overcome Defense Mechanism of Plutella xylostella - Li, Shuzhong; Xu, Xiaoxia; Shakeel, Muhammad; Xu, Jin; Zheng, Zhihua; Zheng, Jinlong; Yu, Xiaoqiang; Zhao, Qian; Jin, Fengliang (Frontiers in Physiology, 2018)
BACKGROUND: Plutella xylostella has become a notorious pest of cruciferous crops all over the world. Bacillus thuringiensis δ-endotoxins are widely used insecticidal proteins for controlling P. xylostella. However, the interaction mechanism of B. thuringiensis with the immune system of P. xylostella, at the genomic level, is still unclear. The present study explored the immune response of P. xylostella to B. thuringiensis, at different time courses, 6, 12, 18, 24, and 36 h, by using RNA-Sequencing and RT-qPCR. RESULTS: In total, 167 immunity-related genes were identified and placed into different families, including pattern recognition receptors, signal modulators, immune pathways (Toll, Imd, and JAK/STAT), and immune effectors. It is worth mentioning that the differentially expressed immunity-related genes analyses exhibited that most of the DEGs (87, 56, 76, 67, and 73) were down-regulated in P. xylostella following B. thuringiensis oral infection at 6, 12, 18, 24, and 36 h, respectively. Interestingly, our RNA-Seq analysis also revealed reduced expression of antimicrobial peptides that play a vital role in the humoral immune system of P. xylostella. CONCLUSION: The results of our study demonstrate a novel role for B. thuringiensis to control P. xylostella via suppressing the immune system.